Constituents from the Branches of Sambucus sieboldiana var. pendula with the Properties of Collagen Synthesis Activation - Jun Hwan Yim, Moon Sik Jang, Mi Yeon Moon, Ha Youn Lee, Sung Chun Kim, Nam Ho Lee (Journal of Applied Pharmaceutical Science, 2015)
For the purpose of developing anti-wrinkle cosmetic ingredients, the extracts from branches of a woody plant Sambucus sieboldiana var. pendula were examined on collagen synthesis activities using fibroblast HDFn cells. As a result, the S. sieboldiana ethanol extract (SSE) proved to activate the production of type I procollagen in a dose-dependent manner without showing cell toxicity. Phytochemical study was conducted to isolate the active constituents in the extracts by solvent fractionation followed by chromatographic purifications. From this procedure, two known compounds, kaempferol 3-O-sophoroside (1) and daucosterol (2), were identified by spectroscopic studies. From the isolates, the flavonoid glycoside 1 was verified to induce the synthesis of the type I procollagen dose-dependently. These results suggested that S. sieboldiana extract containing the flavonoid 1 could be useful as an active ingredient in wrinkle-care cosmetics.
Keywords: Sambucus sieboldiana, collagen, fibroblast, anti-wrinkle.